Rib osteochondroma causing cardiac compression in a pediatric patient - Alnassar, Abdulaziz Sami (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Rib osteochondromas are rare genetic disorders, which can present as bony exostosis causing compression, impingement and damage to surrounding vessels, organs and structures within the thoracic cavity. The objective of this study was to clearly describe a rare presentation of rib osteochondromas in a pediatric patient along with managing techniques. CASE: A 9-year-old girl was admitted to the hospital due to shortness of breath on exertion. Physical examination did not reveal any abnormalities except for small bony projections over the left 5th rib. Computed tomography (CT) scan showed a bony lesion on the left fifth rib causing cardiac compression. Video-assisted thoracoscopy (VAT) was done, which showed a bony exostosis compressing the left ventricle, the lesion was resected without any complications. Final pathology confirmed the diagnosis of osteochondroma measuring 2.0 cm × 2.0 cm × 1.5 cm, along with a thickness of 0.4 cm. Post-operative recovery was well, with no morbidities and the patient was discharged without any complications. On the post-operative follow up, the patient showed significant improvement in her symptoms. CLINICAL DISCUSSION: Our reported case is a rare example of a solitary costal osteochondroma leading to serious complications because of its shape, size, and location. Previous reports have not addressed any significant traumatic event or impact prior to the occurrence of symptoms related to the cases, including the case of our patient. Cases of rib exostosis were surgically approached using different techniques most often through thoracotomy. CONCLUSIONS: Rib osteochondromas are rare benign bony lesions which can cause cardiac symptoms secondary to direct compression. They can be resected safely via video assisted thoracoscopy (VAT) or limited thoracotomy.